1990
DOI: 10.1007/bf00308488
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial ependymomas in children

Abstract: During a 20-year period (1964-1983), the authors managed 60 children with intracranial ependymomas. In 37 patients the tumors were located in the posterior cranial fossa, and in the remaining 23 they were supratentorial. The histological examination in 26 children revealed ependymoblastomas. The average duration of the clinical evolution was 4 months and 5 days in the supratentorial neoplasms and 3 months and 6 days in the subtentorial. Besides the intracranial hypertension, present in about 80% of the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The next step is to determine the impact of these neurological deficits on parameters measuring functional outcomes and quality of life and then to find new ways to reduce surgical morbidity. Surgical morbidity rates in the range of 20 to 36% (9, 10) have previously been reported, and with technological improvements, morbidity rates in modern surgical practice have fallen. For tumors involving the posterior fossa, morbidity has been attributed to radical resection of IVth-ventricle tumors attached to the brainstem (11).…”
Section: Discussionmentioning
confidence: 98%
“…The next step is to determine the impact of these neurological deficits on parameters measuring functional outcomes and quality of life and then to find new ways to reduce surgical morbidity. Surgical morbidity rates in the range of 20 to 36% (9, 10) have previously been reported, and with technological improvements, morbidity rates in modern surgical practice have fallen. For tumors involving the posterior fossa, morbidity has been attributed to radical resection of IVth-ventricle tumors attached to the brainstem (11).…”
Section: Discussionmentioning
confidence: 98%
“…Other series confirmed a poor outcome for posterior fossa ependymomas [12,21,26,39], suggesting that tumor location is important in limiting surgical removal and, consequently, affecting the outcome. In particular, considering fourth-ventricle ependymomas, which in our study accounted for 60% of the tumors, in some series most of the tumors seem to arise in the vestibular area or the lateral recess [8,43].…”
Section: The Role Of Tumor Locationmentioning
confidence: 90%
“…O ften the description of the extent of extirpation is based on the surgeon' s personal view, which is som etim es substantiated by postoperative neuro- The true extent of resection, as con® rm ed with postoperative M RI, should be correlated w ith survival, to use it as a prognostic factor. Som e authors report a better prognosis in a group of patients with a total resection of an intracranial ependym oma 7,12,20,24,27,29,68 or a spinal cord ependym oma. 16,22,39,40,45 Sutton et al 69 even found that the extent of surgical resection is a m ajor determ inant of ® nal outcom e in ependym omas.…”
Section: Surgerymentioning
confidence: 97%
“…7,23,27,29,46,59,63 C. Data obtained from series describing intracranial ependymomas in children only, including supra-and infratentorial ependymomas. 9,26,28,36,68,69,73 D. Data obtained from series describing spinal ependym omas in both adults and children. 38± 41,43,64,66,67,74,81± 82 cervical ® eld extension and local high dose irradiation with local ® elds.…”
Section: Surgerymentioning
confidence: 99%